Optical properties of ion implanted thin Ni films on lithium niobate - Lysiuk, V.O.; Staschuk, V.S.; Androsyuk, I.G.; Moskalenko, N.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Ion implantation by keV Ar⁺ ions creates blisters on the surface of thin Ni films deposited on lithium niobate and causes changes in optical properties and structure of Ni film and lithium niobate substrate. Processes of ion implantation and effects of increasing absorption, adhesion, damage threshold are described and explained in the paper. Development of pyroelectric photodetector “thin Ni film – lithium niobate” is proposed.